RANCANG BANGUN ANTENA MIKROSTRIP RECTANGULAR DENGAN METODE FRACTAL SIERPINSKI UNTUK TEKNOLOGI LONG TERM EVOLUTION 2300 MHz - Eka Setia Nugraha; Ilham Januar Ramdhani; Petrus Kerowe Goran (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2021)
The technology currently developing is Long Term Evolution (LTE) which works at the frequencies of 1800 MHz, 2100 MHz, and 2300 MHz. To support LTE technology, an antenna design that conforms to LTE specifications is needed, one of which is a microstrip antenna that supports Multiple Input Multiple Output (MIMO), which in this type allows it to use more than one antenna, both on the transmitter and receiver ( receiver). Because it is possible to use more than one antenna. In this study, using a MIMO microstrip antenna model with the fractal sierpinski method which aims to increase the value of the bandwidth so that it can perform a fast data transmission. In this antenna, the value of the return loss parameter is obtained with a value of -12.05 dB for antenna 1 and -16.75 dB for antenna 2 measurement results, and in the simulation results produce a value of -14.88 dB, for the impedance value the antenna measurement value is obtained. 1, namely 32.33 Ohm and antenna 2 43.4 Ohm, for the simulation it produces a value of 50 Ohm, for the gain during the simulation it produces a value of 5.084 dB and the measurement results in a value of 2.7 dB, for the simulation bandwidth value is 20 MHz, and at When the measurement of antenna 1 yields a value of 18 MHz and antenna 2 is 15 MHz, and the radiation pattern for the simulation and measurement results shows that the radiation pattern is unidirectional.